Cytoplasmic RRM1 activation as an acute response to gemcitabine treatment is involved in drug resistance of pancreatic cancer cells. - Tomotaka Kato (Public Library of Science (PLoS), 2021)
Background RRM1 is functionally associated with DNA replication and DNA damage repair. However, the biological activity of RRM1 in pancreatic cancer remains undetermined. Methods To determine relationships between RRM1 expression and the prognosis of pancreatic cancer, and to explore RRM1 function in cancer biology, we investigated RRM1 expression levels in 121 pancreatic cancer patients by immunohistochemical staining and performed in vitro experiments to analyze the functional consequences of RRM1 expression. Results Patients with high RRM1 expression had significantly poorer clinical outcomes (overall survival; p = 0.006, disease-free survival; p = 0.0491). In particular, high RRM1 expression was also associated with poorer overall survival on adjuvant chemotherapy (p = 0.008). We found that RRM1 expression was increased 24 hours after exposure to gemcitabine and could be suppressed by histone acetyltransferase inhibition. RRM1 activation in response to gemcitabine exposure was induced mainly in the cytoplasm and cytoplasmic RRM1 activation was related to cancer cell viability. In contrast, cancer cells lacking cytoplasmic RRM1 activation were confirmed to show severe DNA damage. RRM1 inhibition with specific siRNA or hydroxyurea enhanced the cytotoxic effects of gemcitabine for pancreatic cancer cells. Conclusions Cytoplasmic RRM1 activation is involved in biological processes related to drug resistance in response to gemcitabine exposure and could be a potential target for pancreatic cancer treatment.